2003
DOI: 10.1007/s00249-003-0316-9
|View full text |Cite
|
Sign up to set email alerts
|

Conformation of heparin studied with macromolecular hydrodynamic methods and X-ray scattering

Abstract: The hydrodynamic characteristics of heparin fractions in a 0.2 M NaCl solution have been determined. Experimental values varied over the following ranges: the sedimentation coefficient (at 20.0 degrees C), 1.3 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
115
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(131 citation statements)
references
References 26 publications
15
115
1
Order By: Relevance
“…The specific refractive increment of heparin (B in equations below) was determined experimentally. A calibration curve of refractive index versus heparin concentration was constructed, and the best fit value of the slope dñ/dw B ϭ 0.126 cm 3 /g is in agreement with the published values (23,24). A composition gradient was created using the Calypso system (Wyatt, Santa Barbara, CA), in which the fraction of solution A (f A ) is decreased from 1 to 0 in steps of 0.08, and the total concentrations of Tau (A) and heparin (B) in each of these mixtures is given by the following equations.…”
Section: Methodssupporting
confidence: 82%
“…The specific refractive increment of heparin (B in equations below) was determined experimentally. A calibration curve of refractive index versus heparin concentration was constructed, and the best fit value of the slope dñ/dw B ϭ 0.126 cm 3 /g is in agreement with the published values (23,24). A composition gradient was created using the Calypso system (Wyatt, Santa Barbara, CA), in which the fraction of solution A (f A ) is decreased from 1 to 0 in steps of 0.08, and the total concentrations of Tau (A) and heparin (B) in each of these mixtures is given by the following equations.…”
Section: Methodssupporting
confidence: 82%
“…In the course of the NMR conformational studies, it became clear that heparin did not behave in this way (Forster et al, 1989;Mulloy et al, 1993); the quantitative nuclear Overhauser effect values could not be interpreted unless it was assumed that heparin tumbled as an "asymmetric top," specifically as if the shape of the heparin molecules was more like a cylinder than a sphere. Analytical ultracentrifugation and X-ray scattering results were consistent in this assessment (Pavlov et al, 2003) and indicated a semirigid cylindrical structure for heparin oligosaccharides, with flexibility increasing as oligosaccharide length increases .…”
Section: The Conformational and Dynamic Properties Of Heparin (Andsupporting
confidence: 71%
“…Thus, it appears that the heparin binding by the ␣X I domain is a rare case of a Mg 2ϩ ion contributing to protein-heparin interaction. The end-to-end length of heparin either determined from hydrodynamic measurements (25) or direct measurements on heparin in complex with thrombin resolved by x-ray crystallography (26) corresponds to 0.5 nm/monosaccharide unit. dp12 oligomers would thus be assumed to take a length of 6 nm, which is comparable with the diameter of the I domain at 5 nm (12).…”
Section: Discussionmentioning
confidence: 99%